A Need for Context-Based Conservation: Incorporating Local Knowledge to Mitigate Livestock Predation by Large Carnivores - Bijoor, Ajay; Khanyari, Munib; Dorjay, Rigzen; Lobzang, Sherab; Suryawanshi, Kulbhushansingh (Frontiers in Conservation Science, 2021)
Mitigating livestock predation by carnivores is crucial to ensure carnivore conservation and facilitate human-carnivore coexistence. Mitigation measures proposed by conservation agencies, however, are often technocratic and perceived as being an external imposition on the local community. Herders affected by the depredation may have the knowledge to design locally relevant solutions, but they might lack financial and technical support to implement these effectively. Their inability to act can result in the communities being viewed as the antagonist, rather than a part of the solution. We present a case study on co-development of a conservation intervention by a traditional pastoral community together with a conservation NGO, to mitigate livestock depredation inside night-time corrals, in Ladakh, India. Between January and June 2020, livestock corrals in Sumdo village were attacked ten times by carnivores such as snow leopards and wolves, killing over 100 sheep, goat, yak and horses and causing loses of over 10,400 USD between January and June 2020. Local people were agitated and there were strong demands for capture or removal of the carnivores from the area. We operationalized the PARTNERS principles framework for community-based conservation to help the village effectively implement an intervention based on a novel predator-proof corral design conceptualized by the community. We demonstrate that empowering the community to design and implement a conservation intervention helped them take ownership of the effort, improve trust with conservation agencies, and hence likely to be a long-term solution to conservation conflicts in the region. Our approach of using the PARTNER’s principles has relevance for conservation agencies across the world who are trying to implement interventions, in particular those to reduce livestock depredation by carnivores. Our approach further helps the community to view itself as part of the solution and not the problem.